METHODOLOGY AND APPLICATIONS IN POWER TRANSFORMER MONITORING (ELECTRICAL MACHINES, MATERIALS AND DRIVES — PRESENT AND TRENDS, 2025)
This paper presents the importance and applicability of Dissolved Gas Analysis (DGA) for monitoring the health of power transformers, essential in electrical distribution networks. The reliability of transformers is critical, and DGA represents an effective method for early detection of internal faults by measuring dissolved gases in the insulating oil. Different interpretation techniques, such as the Duval Triangle and Roger methods, are discussed for identifying fault types based on the concentration and ratio of the resulting gases. The paper also explores the limitations of these methods and future perspectives, proposing a multi-method approach based on machine learning algorithms to improve the accuracy and consistency of DGA interpretation.DOI: https://doi.org/10.36801/apme.2024.1.14
Keywords: Dissolved sas analysis (DGA); Power transformers; Transformer condition monitoring; Electrical and thermal faults; Insulating oil; Partial electrical discharges; Electric arc; IEEE standards; DGA interpretation; Predictive maintenance